2013
DOI: 10.1590/sajs.2013/1274
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable oil based liquid nanocomposite dielectric

Abstract: Physically smaller dielectric materials would improve the optimisation of space for power systems. Development of nanotechnology provides an effective way to improve the performances of insulating oils used in power system applications. In this research study, we focused on the development of nanomodified vegetable oils to be used in power transformers. Higher conduction currents were observed in virgin linseed oil than in virgin castor oil. However, for both virgin linseed and virgin castor oil, the DC conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…The SEM technique is used to observe the morphology of the silica aerogel particles in the acrylic resin bulk. The similar structure of the aerogel particles can be observed in the research studies carried out by Chetty et al . and Gupta and Ricci .…”
Section: Resultssupporting
confidence: 81%
“…The SEM technique is used to observe the morphology of the silica aerogel particles in the acrylic resin bulk. The similar structure of the aerogel particles can be observed in the research studies carried out by Chetty et al . and Gupta and Ricci .…”
Section: Resultssupporting
confidence: 81%
“…The fact that, these nanoparticles do not always improve the dielectric strength of natural ester, has been also reported by others [32]. By considering virgin linseed and virgin castor, Chetty et al [32] observed that the addition of 5 wt% of silica aerogel powder nanoparticles increased the streamer activity.…”
Section: Discussionmentioning
confidence: 74%
“…The volume resistivity of nano-modified vegetable oil [73], [143] and BN or Fe 2 O 3 modified insulating oil has been analyzed over frequency [87]. The resistivity influence on nanoparticle of silica aerosol on castor oil can be a measurement of DC conduction current [147], [148].…”
Section: B Dielectric Analysismentioning
confidence: 99%